(untitled) (Italian Journal of Public Health, 2012)
Background: adolescent migrants are in a state of double vulnerability because of their age and migration experience. The purpose of this review was to identify risk and protective factors serving as a base for health promotion of young recent migrants. Methods: we assessed 95 papers identified through a MEDLINE search. Thirty-five papers were retained for review and analysed within the following themes: general health, mental health, cigarette smoking and sexual health. Results: young migrants’ health was considered good at arrival, but deteriorated with length of stay due to factors linked to migration. Mental health was determined by pre-migration factors, such as violence, and was strongly related to post-migration factors, such as asylum procedures, discrimination and low socio-economic status. Social support and family cohesion were identified as protective factors. We found a lack in epidemiologic data about tobacco use and sexual health issues. Results from North America indicated less frequent smoking in certain groups of immigrants. Some data suggested more frequent teenage pregnancies and abortions in young refugee women as compared to the host population. We also found some evidence about increased risk of sexually transmitted infections and HIV/AIDS in certain immigrant populations. Conclusions: migrant adolescents are generally healthy at arrival. The migration process and social inequalities after arrival influence their long-term health. A comprehensive approach to health promotion is necessary, taking into account risk and protective factors. More research is needed, in order to obtain more specific epidemiologic data about adolescent migrants, as well as longitudinal and qualitative data.